The Influence of Think Pair Share Cooperative Learning Models on Outcome in Integrated Thematic Learning for Grade V Elementery School - Yuri Yuliajati Putri; Reinita Reinita (Universitas Muhammadiyah Enrekang, 2022)
The goal of this research is to see how the Think Pair Share (TPS) cooperative model affects student learning outcomes in integrated theme learning in class V Cluster I, Jurai District IV. This study used a non-equivalent control group design, which is a type of quasi-experimental methodology. This research covered all pupils in class V Cluster I, Jurai District IV. The experimental and control classes were created through purposeful sampling, with class V A acting as the experimental class and class V B functioning as the control class. The hypothesis was evaluated with a t test at a 95% confidence level (α = 0.05), and the results indicated that tcount > ttable (2,434 > 2,045), showing that H1 is correct. As a consequence, using the Think Pair Share (TPS) cooperative learning technique in integrated theme learning in class V of Elementary School had a significant influence on student learning outcomes.